An Analysis of The Implied Meaning of Love in Robert Burn’s Poem “A Red, Red Rose” (Structural Analysis) - Tuna, Ayu Aprilia; Katili, Adriansyah Abu; Muhamad, Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the implied meaning of love in Robert Burns’ A Red, Red Rose through a structural approach, integrating Cognitive Poetics, Conceptual Metaphor Theory, and structuralist perspectives. Using qualitative analysis, each stanza is explored to identify figurative devices such as similes, hyperboles, symbolism, repetition, rhyme, and meter, and to interpret how these elements convey nuanced emotional meanings. The findings reveal that stanza 1 presents love as fresh and harmonious; stanza 2 emphasizes its enduring nature across time; stanza 3 expresses a cosmic and temporal climax; and stanza 4 depicts a dignified farewell, highlighting constancy, hope, and devotion. Overall, Burns’ integration of figurative language and structural patterns demonstrates love as eternal, resilient, and harmoniously balanced. Suggestions for future research include applying cognitive and cross-cultural approaches to poetry, while educators and students are encouraged to analyze the interplay of form and figurative devices to deepen understanding of implied meaning.